Tasawuf Qur’ani sebagai Terapi Spiritual terhadap FOMO di Era Digital - Aslam Habibi; Norhidayat; Ahmad Mujahid (PT. Hasba Edukasi Mandiri, 2026)
The phenomenon of Fear of Missing Out (FOMO) in digital culture is generally examined through psychological and sociological approaches, while studies on tasawwuf (Islamic mysticism) remain largely normative and have not yet been formulated as a systematic therapeutic framework. This study aims to analyze Qur’an-based tasawwuf as a psychospiritual therapeutic paradigm for addressing FOMO-related anxiety as a symptom of the crisis of inner orientation in modern humanity. The research employs a descriptive qualitative method through library research, utilizing a thematic-contextual hermeneutical approach to relevant Qur’anic verses, combined with critical engagement with classical and contemporary tasawwuf literature. The findings indicate that Qur’anic tasawwuf functions not merely as a form of spiritual ethics, but as a psychospiritual therapeutic framework operating through the reconstruction of life-meaning orientation from external validation toward Divine consciousness, the regulation of digital narcissistic impulses through mujahadah and riyadhah, and the management of existential anxiety through the internalization of tawakkul, qana‘ah, and dhikr. Conceptually, this study proposes that FOMO represents a manifestation of nafs al-ammarah within the digital context, whereas Qur’anic tasawwuf serves as a transformative process toward al-nafs al-muthmainnah. This study affirms the relevance of Qur’anic tasawwuf as a contextual and applicable spiritual therapeutic approach to addressing human anxiety in the digital era.